Effectiveness Of Static Exercise Therapy And Friction Massage In Increasing Joint Range Of Motion And Reducing Pain And Reducing Pain - Setiawan, Arif; Aziz, Zainul; Priyanto, Priyanto (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Joint disorders are one of the most common health problems in the community, whether due to injury, degenerative disease or excessive physical activity. These conditions often lead to reduced range of motion and increased joint pain, which can have a negative impact on quality of life. This study aimed to evaluate the effectiveness of static exercise and effriction massage therapy in improving joint mobility and reducing pain in patients with joint disorders. The research used a pre-experimental design with a one-group pretest-posttest model. The sample consisted of 30 adults with lower back pain selected by purposive sampling. Participants received two interventions effraction massage focused on the lumbar region of the back and static exercises. The massage was administered by a therapist for 15 minutes and focused on the lumbar region. Pain levels and functional movement were measured before and after the interventions using the Visual Analogue Scale (VAS) and the Oswestry Disability Index (ODI). Data were analysed using paired t-tests. The results of this research data show that there is effectiveness of static exercise and mass effriction on the recovery of back pain perception in athletes with a t-count value of 15.07, an average of 6.58 and 95% confidence interval level with the lowest value of 3.95 and the highest value of 7.33. There are significant results of static flexibility training to increase the flexibility of the back in athletes with a t-count value of 5.68, an average of 2.49 and 95% confidence interval level with the lowest value of 1.64 and the highest value of 3.47.The conclusion of the study showed that massage effriction and flexibility training can provide changes in the perception of pain and flexibility of the back in athletes.